2002
DOI: 10.1046/j.1365-2427.2002.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of nutrients to rooted submerged macrophytes growing in a nutrient‐rich stream

Abstract: 1. The relative contribution of roots and leaves to nutrient uptake by submerged stream macrophytes was tested in experiments where plants were grown in an outdoor flow‐channel system. Water was supplied from a nutrient‐rich stream with inorganic nitrogen and phosphorus concentrations typical of Danish streams. 2. Four submerged macrophyte species were tested, Elodea canadensis, Callitriche cophocarpa, Ranunculus aquatilis and Potamogeton crispus, and all species were able to satisfy their demand for mineral n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
123
5
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(133 citation statements)
references
References 35 publications
4
123
5
1
Order By: Relevance
“…Madsen and Cedergreen, 2002), there seems to be no consistent relationship between nutrient concentrations in the water column and growth parameters in the literature. Some studies find a lack of relationship between nutrient loading and macrophyte growth (Madsen and Cedergreen, 2002) while other report such a relationship (Wersal and Madsen, 2011;O'Hare et al, 2010). The reason for this might be that the available nutrients satisfy the nutrient requirements for maximum growth and therefore additional nutrients do not result in higher growth rates (Madsen and Cedergreen, 2002).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Madsen and Cedergreen, 2002), there seems to be no consistent relationship between nutrient concentrations in the water column and growth parameters in the literature. Some studies find a lack of relationship between nutrient loading and macrophyte growth (Madsen and Cedergreen, 2002) while other report such a relationship (Wersal and Madsen, 2011;O'Hare et al, 2010). The reason for this might be that the available nutrients satisfy the nutrient requirements for maximum growth and therefore additional nutrients do not result in higher growth rates (Madsen and Cedergreen, 2002).…”
Section: Discussionmentioning
confidence: 89%
“…While macrophytes are commonly able to satisfy their nutrient requirements from the water column (e.g. Madsen and Cedergreen, 2002), there seems to be no consistent relationship between nutrient concentrations in the water column and growth parameters in the literature. Some studies find a lack of relationship between nutrient loading and macrophyte growth (Madsen and Cedergreen, 2002) while other report such a relationship (Wersal and Madsen, 2011;O'Hare et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al (2005) have suggested that the root morphology of V. natans varies considerably with the fertility of the sediment in which it grows. A marked effect of the nutrients in the water column on the growth of submerged macrophytes has been reported to be reduced root biomass (Rattray et al, 1991;Madsen and Cedergreen, 2002). Indeed, root morphology can be greatly affected by nutrient availability in the environment and by the nutrient status of the plant (Linkohr et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, re-vegetation of V. natans improved the water quality slightly more than sediment capping alone. It is possible that the fertile sediments diminished the uptake of N and P nutrients from water by the plants (Squires and Lesack, 2003;Rooney et al, 2003) and the experimental period was not long enough for the recruitment of algal grazers (Estlander et al, 2009;Zhao et al, 2013), although submerged macrophytes were reported to improve the water quality through multiple mechanisms, such as taking up nutrients, stabilizing sediment, sheltering algae-filtering zooplanktons and competing with phytoplankton for light and nutrients (Scheffer et al, 1993;Madsen and Cedergreen, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…They improve the water quality by ways of absorbing nutrients, stabilizing sediment, sheltering algae-filtering zooplanktons and competing with phytoplankton for light and nutrients (Scheffer et al, 1993;Qiu et al, 2001). Rooted submerged macrophytes absorb nutrients by both shoots and roots, but the relative importance of sediment versus overlying water as N and P sources for the plants varies among species and depends on nutrients concentrations in the water and sediment (Madsen and Cedergreen, 2002;Xie et al, 2005;Cao et al, 2011). The submerged macrophyte Vallisneria natans is a perennial species with a large amount of roots, that prefers mesotrophic to eutrophic water.…”
Section: Introductionmentioning
confidence: 99%